CONTRIBUTION OF RESERVATION THROUGH TRAVEL AGENT TO ROOM OCCUPANCY AT LE GRANDE BALI - Ni Made Novi Cipta Dewi; I Nyoman Rajin Aryana; Ni Made Ernawati; Ni Nyoman Sri Astuti; I Ketut Suarta (Politeknik Negeri Bali, 2018)
Travel agent is a business engaged in the field of service and provides information about all things related to travel. The purpose of this study is to find out how the application of travel agent reservation with room occupancy at Le Grande Bali and to know the comparison of travel agent reservation and room occupancy at Le Grande Bali. The rationale to discuss this topic in this research with the title